Ormeloxifene nanotherapy for cervical cancer treatment - Chauhan N (Dove Medical Press, 2019)
Neeraj Chauhan1,2, Diane M Maher3, Bilal B Hafeez1,2, Hassan Mandil1, Man M Singh4, Murali M Yallapu1,2, Meena Jaggi1,2, Subhash C Chauhan1,2 1Department of Pharmaceutical Sciences, University of Tennessee Health Science Center, Memphis, TN 38163, USA; 2Department of Immunology and Microbiology, School of Medicine, University of Texas Rio Grande Valley, McAllen, TX 78504, USA; 3Sanford Research Center, USD, Sioux Falls, SD 57104, USA; 4Research and Development, Saraswati Dental College, Lucknow, Uttar Pradesh, IndiaCorrespondence: Meena Jaggi; Subhash C ChauhanDepartment of Immunology and Microbiology, School of Medicine, University of Texas Rio Grande Valley, McAllen, TX 78504, USATel +1 956 296 1926; +1 956 296 5000Email meena.jaggi@utrgv.edu; subhash.chauhan@utrgv.eduBackground: Cervical cancer (CxCa) ranks as the fourth most prevalent women-related cancer worldwide. Therefore, there is a crucial need to develop newer treatment modalities. Ormeloxifene (ORM) is a non-steroidal, selective estrogen receptor modulator (SERM) that is used as an oral contraceptive in humans. Recent investigations suggest that ORM exhibits potent anti-cancer activity against various types of cancers. Nanoparticulates offer targeted delivery of anti-cancer drugs with minimal toxicity and promise newer approaches for cancer diagnosis and treatment. Therefore, the nanotherapy approach is superior compared to traditional chemotherapy, which is not site-specific and is often associated with various side effects.Methods: Pursuing this novel nanotherapy approach, our lab has recently developed ORM-loaded poly [lactic-co-glycolic acid] (PLGA), an FDA-approved biodegradable polymer, nanoparticles to achieve targeted drug delivery and improved bioavailability. Our optimized PLGA-ORM nanoformulation showed improved internalization in both dose- and energy-dependent manners, through endocytosis-mediated pathways in both Caski and SiHa cell lines. Additionally, we employed MTS and colony forming assays to determine the short- and long-term effects of PLGA-ORM on these cells.Results: Our results showed that this formulation demonstrated improved inhibition of cellular proliferation and clonogenic potential compared to free ORM. Furthermore, the PLGA-ORM nanoformulation exhibited superior anti-tumor activities in an orthotopic cervical cancer mouse model than free ORM.Conclusion: Collectively, our findings suggest that our novel nanoformulation has great potential for repurposing the drug and becoming a novel modality for CxCa management.Keywords: CxCa, ORM, PLGA, nanoformulation